2022
DOI: 10.3390/vaccines10030377
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Liver Cirrhosis Show High Immunogenicity upon COVID-19 Vaccination but Develop Premature Deterioration of Antibody Titers

Abstract: SARS-CoV-2 infection is known to lead to severe morbidity and mortality in patients with liver cirrhosis. For this reason, vaccination of these patients against COVID-19 is widely recommended. However, data regarding immunogenicity in patients with liver cirrhosis is limited and even less is known about the kinetics of antibody response, as well as the optimal timing of booster immunization. We analyzed immunogenicity in 110 patients with liver cirrhosis after receiving two doses of the mRNA-based vaccine BNT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 44 publications
2
36
2
2
Order By: Relevance
“…Although a weaker immune response upon COVID-19 vaccination has been described for particular groups, like elderly or immune-compromised individuals ( 10 13 ), we observed differences in immune response independent from these factors. Genetic variations might explain some of the differences in the strength of innate immune response ( 14 ).…”
Section: Discussioncontrasting
confidence: 53%
“…Although a weaker immune response upon COVID-19 vaccination has been described for particular groups, like elderly or immune-compromised individuals ( 10 13 ), we observed differences in immune response independent from these factors. Genetic variations might explain some of the differences in the strength of innate immune response ( 14 ).…”
Section: Discussioncontrasting
confidence: 53%
“…Some evidence suggests that the antibody titers induced by mRNA vaccines in patients with cirrhosis may be lower than that in healthy individuals without liver disease [ 26 ]. Further, Thuluvath et al reported suboptimal antibody responses in 19% patients with optimal antibody levels in 77.2% of 79 patients with cirrhosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine immunogenicity Patients with CLD have been shown to have anti-SARS-CoV-2 S-spike IgG seroconversion rates of >85% following two vaccine doses [281]. However several studies have suggested that patients with cirrhosis may have a more rapid decline in antibody titers over time compared to healthy controls [281,282]. In contrast, LT recipients remain at high-risk for suboptimal humoral responses to vaccination.…”
Section: Vaccine Responsiveness In Patients With Cld and In Liver Tra...mentioning
confidence: 99%